Family Empowerment Model Based On Socio-Cultural Wisdom For Stunting Prevention In North Gorontalo Regency - Nasaru, Jumriyanti; Azam, Mahalul; Woro Kh, Oktavia; Yuniastuti, Ari (International Journal of Health Literacy and Science, 2025)
Stunting prevalence affects 149.2 million children worldwide, compromising cognitive development and economic productivity. North Gorontalo Regency experienced an increase in prevalence from 23.6% to 30.5% between 2022 and 2023, highlighting the limitations of conventional interventions. This quasi-experimental study evaluated culturally integrated health promotion models through family empowerment among 384 households with children aged 0-59 months in North Gorontalo Regency. The study employed intervention groups (n=192) and control groups (n=192) using statistical and thematic analytical approaches. Interventions integrated Nola Pender's Health Promotion Model with indigenous Gorontalo socio-cultural wisdom through two-month participatory education programs and enhanced interpersonal communication strategies. Findings revealed substantial behavioral transformations: family knowledge scores improved by 34.2% (p<0.001), positive attitudes toward traditional feeding practices increased by 28.7% (p<0.01), and optimal childcare practice adoption rose by 42.1% (p<0.001) compared to control groups. The culturally adapted model effectively leveraged indigenous childcare wisdom and community social frameworks, achieving sustainable behavioral changes that integrate traditional practices with evidence-based stunting prevention approaches, thereby enhancing program acceptance and effectiveness.